Mechanism and Kinetics of the Ethylene Removal in Flue Gas by Ozone Injection - Wen, Zhengcheng; Wang, Zhihua; Xu, Jiangrong; Zhou, Junhu; Cen, Kefa (Asian Journal of Chemistry, 2010)
The ozone injection is one of the promising technologies to remove multi-pollutants such as NOx, SO2, Hg and VOCs in flue gas simultaneously. However, little attention has been paid to the mechanism and kinetic of the volatile organic compounds (VOCs) removal during ozone injection. As well known, quantum chemical calculation is an effective means for mechanism and kinetic studies. Therefore, the mechanism and kinetic of the volatile organic compounds removal in flue gas by ozone injection were investigated in detail by employing quantum chemical calculation. Based on geometry optimizations made by B3LYP/6-31G (d) method, the microcosmic reaction processes were analyzed and depicted in detail and the reaction activation energies were calculated by QCISD(T)/6-311g(d,p) method. Moreover, the kinetic parameters of the reactions were calculated by the classical transition state theory. Results showed that, the activation energies of the C2H4 + O3 and C2H4 + NO3 reactions were 6.58 and 6.66 kcal/mol, respectively and the Arrhenius expressions of these two reactions were k = 9.45 × 1011 exp(-30834/RT) and k = 9.47 × 1012 exp (-31111/RT) (cm3 mol-1 s-1), respectively. The calculated activation energies and kinetic parameters were in good agreement with the experimental results, which indicated the mechanism and kinetic study by employing quantum chemical calculation was reasonable and reliable.